Effect of Microwave Pretreatment on the Antioxidant Activity and Stability of Enzymatic Products from Milk Protein - Xue Yang; Xiaofeng Ren; Haile Ma (Foods, 2022)
The effects of microwave pretreatment on the antioxidant activity and stability of enzymatic products from milk protein (MP) were studied. The peptide content, molecular weight distribution, and amino acid composition of MP hydrolysate were also measured to explain the change of antioxidant activity under microwave pretreatment. The results showed that microwave pretreatment increased the degree of hydrolysis of MP with the power of 400 W for the highest value. The DPPH scavenging activity and the total antioxidant capacity of MP pretreated by microwave with a power of 300 W presented the highest effect and increased by 53.97% and 16.52%, respectively, compared to those of control. In addition, the results of thermal stability and in vitro digestion of MP hydrolysate showed that the MP hydrolysate pretreated by microwave exerted excellent antioxidative stability, especially for the microwave power of 300 W. After pretreated with microwave, the peptide content increased as the rise of power and it reached the peak at the power of 400 W. The molecular weight of MP hydrolysate pretreated by microwave with the power of 300 W showed more percentage of peptides between 200 Da and 500 Da. The result of amino acid composition showed that total amino acid (TAA) content of MP hydrolysate pretreated by microwave with power of 400 W showed the highest value, which increased by 7.58% compared to the control. The ratio of total hydrophobic amino acids to the TAA of MP hydrolysate showed the most increased amplitude with the microwave power of 300 W. The antioxidant activity of MP hydrolysate was related to the peptide content, and it was also relevant to the amino acid category and content. In conclusion, microwave pretreatment is an effective method for the preparation of antioxidant peptides and an increase in antioxidant stability.